2019
DOI: 10.1186/s13071-019-3302-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic diversity of Acanthamoeba strains isolated from Chilean patients with Acanthamoeba keratitis

Abstract: BackgroundAcanthamoeba spp. are the causative agents of a severe keratitis occurring mainly in contact lens wearers. The genus comprises more than 24 species that are currently divided into 20 different genotypes (T1-T20) according to sequence variations in the 18S rRNA gene. The objective of this study was to identify the genotypes and sub-genotypes of Acanthamoeba isolates collected at the Parasitology Laboratory of the Public Health Institute of Chile, the only laboratory in the country where Acanthamoeba s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Similar to other environmental studies where the genotype T4 of Acanthamoeba spp. was reported as the predominant genotype [44][45][46], the current study found that 3/4 (75%) of sequenced strains were T4 genotype irrespective of the sample site in bathrooms. Additionally, one isolate from the shower curtain/door was identified as A. castellanii T3.…”
Section: Discussionsupporting
confidence: 52%
“…Similar to other environmental studies where the genotype T4 of Acanthamoeba spp. was reported as the predominant genotype [44][45][46], the current study found that 3/4 (75%) of sequenced strains were T4 genotype irrespective of the sample site in bathrooms. Additionally, one isolate from the shower curtain/door was identified as A. castellanii T3.…”
Section: Discussionsupporting
confidence: 52%
“…Acanthamoeba triangularis ( A. triangularis ) is a free-living protozoan ubiquitously found in nature, such as water and soil. The parasite is a causative agent of several diseases, including granulomatous amoebic encephalitis ( Kalra et al, 2020 ) and Acanthamoeba keratitis ( Jercic et al, 2019 ). In keratitis disease, severe vision loss and complete blindness caused by parasites are the main case in contact lens users ( Lee et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…refrigeration systems following a legionellosis outbreak in and around a hospital reported the presence of nine Acanthamoeba isolates belonging to the T4 genotype, which had amoeba resistant bacteria in its interior, emphasizing the importance of these amoebas as bacterial vehicles (Scheikl et al, 2016). All genotypes identified in our study are associated with cases of human infections (Siddiqui and Khan, 2012;Jercic et al, 2019). These results deserve special attention from the hospital community, considering the isolation environment, the characteristic of many patients in a hospital environment, as they may be immunologically susceptible to infections, as well as the opportunistic nature of Acanthamoeba spp.…”
mentioning
confidence: 57%
“…Some studies relate the T11 genotype to cases of amoebic keratitis (Hajialilo et al ., 2016; Jercic et al ., 2019). This was one of the genotypes described as causing this infection in a large research carried out in Austria that included cases of Acanthamoeba infections in the last 20 years (Walochnik et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation